The Host Peritoneal Cavity Harbors Prominent Memory Th2 and Early Recall Responses to an Intestinal Nematode - Yordanova, Ivet A.; Jürchott, Karsten; Steinfelder, Svenja; Vogt, Katrin; Krüger, Ulrike; Kühl, Anja A.; Sawitzki, Birgit; Hartmann, Susanne (Frontiers in Immunology, 2022)
Intestinal parasitic nematodes affect a quarter of the world’s population, typically eliciting prominent effector Th2-driven host immune responses. As not all infected hosts develop protection against reinfection, our current understanding of nematode-induced memory Th2 responses remains limited. Here, we investigated the activation of memory Th2 cells and the mechanisms driving early recall responses to the enteric nematode Heligmosomoides polygyrus in mice. We show that nematode-cured mice harbor memory Th2 cells in lymphoid and non-lymphoid oragans with distinct transcriptional profiles, expressing recirculation markers like CCR7 and CD62-L in the mesenteric lymph nodes (mLN), and costimulatory markers like Ox40, as well as tissue homing and activation markers like CCR2, CD69 and CD40L in the gut and peritoneal cavity (PEC). While memory Th2 cells persist systemically in both lymphoid and non-lymphoid tissues following cure of infection, strikingly specifically peritoneal memory Th2 cells displayed an initial prominent expansion and strong parasite-specific Th2 responses during early recall responses to a challenge nematode infection. This effect was paralleled by a significant influx of dendritic cells (DC) and eosinophils, both also appearing exclusively in the peritoneal cavity of reinfected mice. In addition, we show that within the peritoneal membrane lined by peritoneal mesothelial cells (PeM), the gene expression levels of cell adhesion markers VCAM-1 and ICAM-1 decrease significantly in response to a secondary infection. Overall, our findings indicate that the host peritoneal cavity in particular harbors prominent memory Th2 cells and appears to respond directly to H. polygyrus by an early recall response via differential regulation of cell adhesion markers, marking the peritoneal cavity an important site for host immune responses to an enteric pathogen.